RC beams strengthened by RC jacketing under load - Zinoviy Blikharskyy (Acta Scientiarum Polonorum. Architectura)
This article is devoted to experimental researches of the reinforced concrete beams strengthened by a RC jacketing under load. The program of experimental researches of reinforced concrete beams was envisaged to test four series with a total number of 16 beams 2,100 mm long, of which 14 reinforced beams were additionally pre-loaded. In all experimental samples the longitudinal working reinforcement were steel bars of 2 ∅14 mm А500С. The beams were reinforced by jacketing with the use of two unstressed reinforcement rods of 2 ∅10 A500C mm. To simulate the real life conditions, the loading levels of 30%, 50%, 70% and 90% of the non-strengthened beam bearing capacity were maintained during jacketing. The strengthening effect decreased from 92 to 76% depending on the actual load level (30–90% of the load-bearing capacity of non-strengthened beams). The results of the study could be taken into account in designing reinforced concrete beams strengthened by a RC jacketing under previous loading.